Study on Influencing Factors of Micro and Small Enterprises’ Work Safety Behavior in Chinese High-Risk Industries - Li, Wen; Ni, Xitao; Zuo, Xiaolin; Liu, Suxia; Mei, Qiang (Frontiers in Psychology, 2022)
Due to the limited work safety resources and the poor awareness of work safety from business owners with absolute decision-making power, safety accidents frequently occur in Chinese micro and small enterprises (MSEs) in high-risk industries. This study identifies the influencing factors of work safety behavior from MSEs, government safety supervision department and work safety service agencies. Based on the theory of planned behavior (TPB), the mechanism model of work safety behavior is built from the aspects of behavior attitude, subjective norms, behavior control cognition, past behaviors, and risk awareness of enterprise. After interviewed with nearly 600 MSEs in east of China over six months, the results show that the work safety awareness of the business owner determines the work safety lever of the enterprise, and the work safety behavior of MSEs is a passive restraint behavior. Our findings provide a new perspective on the formation of MSEs’ work safety behavior in high-risk industries.